The microflora of Blue Stilton cheese - Whitley, Elizabeth (2002)
Blue Stilton is a blue-veined cheese manufactured in a restricted area of the UK, using lactic starter cultures plus a secondary culture of Penicillium roquefotti. The aim of this study was to determine the change in microflora during ripening of the cheese and to investigate potential microbial interactions. Additionally, the volatile compounds present in mature samples of cheeses exhibiting few blue veins were compared with those in good quality cheeses, showing ample blue veining.